Hepatic Resection for Hepatocellular Carcinoma in Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis of 7226 Patients. Issue 2 (3rd June 2021) - Molinari, Michele; Kaltenmeier, Christof; Samra, Patrick-Bou; Liu, Hao; Wessel, Charles; Lou Klem, Mary; Dharmayan, Stalin; Emmanuel, Bishoy; Al Harakeh, Hasan; Tohme, Samer; Geller, David; Tevar, Amit; et al.
Abstract : Objective: To systematically review and compare the overall (OS) and disease-free (DFS) survival after hepatic resections for hepatocellular carcinoma (HCC) of patients with nonalcoholic fatty liver disease (NAFLD) versus other risk factors. Background: Different clinical and tumor characteristics are associated with HCC in the setting of NAFLD in comparison to other risk factors. It is still unclear whether these differences impact patient survival after radical hepatectomies. Methods: Randomized controlled trials and observational studies published in the English literature between July 1980 and June 2020 were searched using multiple databases. Patients' baseline characteristics and the hazard ratios (HRs) of the OS and DFS were extracted and meta-analyses were performed. Results: Fifteen retrospective cohort studies with a total of 7226 patients were included. Among them, 1412 patients (19.5%) had NAFLD and 5814 (80.4%) had other risk factors (eg, viral hepatitis B or C, alcoholic cirrhosis, or cryptogenic cirrhosis). Summary statistics showed that patients with NAFLD had better DFS (HR = 0.81; 95% CI: 0.70–0.94; P = 0.006) and OS (HR = 0.78; 95% CI: 0.67–0.90; P = 0.001) than the control group. Subgroups analyses also indicated that the OS favored NAFLD patients versus patients with viral hepatitis B or C (HR = 0.80; 95% CI: 0.67–0.96; P = 0.017) or alcoholic and cryptogenic cirrhosis (HR = 0.68; 95% CI: 0.47–1.0; P = 0.05). Conclusion: After hepatic resections for HCC, NAFLD patients have better DFS and OS than patients with other risk factors. Subgroup analysis and meta-regression suggested that the survival advantage of NAFLD patients was more pronounced in studies published after 2015 and from Asian centers. Abstract : Mini Abstract: This meta-analysis examines the disease-free survival (DFS) and the overall survival (OS) of NAFLD patients undergoing hepatic resection for hepatocellular carcinoma compared to patients with other risk factors. The summary statistics from data extracted from fifteen observational studies suggest that NAFLD patients have more favorable DFS and OS than the control group. Supplemental Digital Content is available in the text.